A Quaternary fault database for central Asia - Mohadjer, Solmaz; Ehlers, Todd Alan; Bendick, Rebecca; Stübner, Konstanze; Strube, Timo (Natural hazards and earth system sciences, 2016)
Earthquakes represent the highest risk in terms of potential loss of lives and economic damage for central Asian countries. Knowledge of fault location and behavior is essential in calculating and mapping seismic hazard. Previous efforts in compiling fault information for central Asia have generated a large amount of data that are published in limited-access journals with no digital maps publicly available, or are limited in their description of important fault parameters such as slip rates. This study builds on previous work by improving access to fault information through a web-based interactive map and an online database with search capabilities that allow users to organize data by different fields. The data presented in this compilation include fault location, its geographic, seismic, and structural characteristics, short descriptions, narrative comments, and references to peer-reviewed publications. The interactive map displays 1196 fault traces and 34 000 earthquake locations on a shaded-relief map. The online database contains attributes for 123 faults mentioned in the literature, with Quaternary and geodetic slip rates reported for 38 and 26 faults respectively, and earthquake history reported for 39 faults. All data are accessible for viewing and download via http://www.geo.uni-tuebingen.de/faults/. This work has implications for seismic hazard studies in central Asia as it summarizes important fault parameters, and can reduce earthquake risk by enhancing public access to information. It also allows scientists and hazard assessment teams to identify structures and regions where data gaps exist and future investigations are needed.